Tinjauan Yuridis Polemik Pinjaman Online (Pinjol) sebagai Alternatif Pembayaran SPP dan Uang Kuliah Tunggal (UKT) bagi Mahasiswa - Nilam Candri Andini; Nooraini Dyah Rahmawati (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This article examines the juridical aspects of online loans (pinjol) as an alternative method for Indonesian students to pay tuition fees (SPP and UKT), with a focus on the partnership between universities and fintech institutions like Danacita. Using normative legal methods and literature analysis, the study finds that while online lending platforms are legally regulated under POJK No. 77/POJK.01/2016, there are still gaps in legal protection for students as consumers. The lack of targeted consumer protection, transparency, and financial literacy raises serious risks of over-indebtedness and academic dropout. This paper calls for more stringent government oversight, improved regulatory enforcement by OJK, and the development of accessible, fair educational financing alternatives.